A new theory for soil health - Harris, Jim A.; Evans, Daniel L.; Mooney, Sacha J. (Wiley, 2022)
The term “soil health” has captured the interest of government, and land managers, whilst the academic community has struggled to rationalise its use and wider benefit. It has proved a powerful tool in conveying best practice to a lay audience. However, the widespread adoption of the “metaphor” has resulted in calls for tools that facilitate the measurement of soil health, preferably quantitatively, and often as a single figure, for ease of use/communication and cost of monitoring. The insurmountable problem is that soil health is neither a readily quantifiable nor measurable object. Only organisms can have ‘health’, which manifests as characteristics of a living system—true of complex systems exhibiting “emergent” properties such as resilience in the face of perturbation. We pose the key question: is soil really a system capable of exhibiting “health”, or any other property emerging from a complex, connected, self-regulating system? We argue that if you cannot detect emergent properties, you are: (i) looking at the wrong dynamic parameter; (ii) not considering the entire system; or (iii) not evaluating at a system at all. We suggest that our focus should instead be on the relationships between components, complexity, and function. Using this as a basis for a new framework will allow us to assemble and align disparate threads of soil science into a cogent and coherent “new theory of soil health”, which is an essential and practical step forward for the sustainable management of global soil resources, across all land uses.
Keywords: Soil health; emergent properties; resilience; systems; scale; dynamic properties